The role of social media on the performance of micro, small and medium enterprises (MSMEs) in Palembang City / Yulizar Kasih and Idham Cholid - -, Yulizar Kasih; -, Idham Cholid (UiTM Cawangan Johor, 2019)
MSMEs have a strategic position and have an important role in the economy of a country, but nowadays the challenges of the development of information technology, especially related to utilizing social media in marketing. This research aims to analyse the use of social media and its benefits for the performance of MSMEs. This research is a descriptive study and 40 samples of MSMEs owners were selected through purposive and convenience sampling technique. The data were collected with questionnaire and analysed descriptively by using tabulations and graphs. The results of this research indicate that the most widely used social media is Instagram, followed by WhatsApp, Facebook, and Line. Social media is used predominantly to facilitate interaction with customers, provide the product information, reduce costs, implement marketing strategies, and to gain product popularity. The use of social media can increase the interaction with customers, sales volume, a good image of customers, and to increase the number of customers.